THE EFFECTIVENESS OF THE "BOMB" METHOD (BREASTCARE, OXYTOCIN MASSAGE, AND MARMET TECHNIQUE) ON INCREASING BREAST MILK PRODUCTION IN BREASTFEEDING MOMENTS AGE 0-6 MONTHS AT PRAMBON PUBLIC HEALTH CLINIC, NGANJUK DISTRICT - siti mudrikatin; Dwi Retno Wati (INTERNATIONAL JOURNAL OF NURSING AND MIDWIFERY SCIENCE (IJNMS), 2020)
The problem experienced by breastfeeding mothers is that the milk is not released on the first to the third day post partum. As a result, newborns who are supposed to be breastfed early will be delayed and as an alternative are given formula milk. The smoothness of the process of lactation or the production and production of breast milk is influenced by breast care, frequency of breastfeeding, maternal psychology, maternal health, and contraception, as well as breast milk production, which is strongly influenced by physical, psychospiritual, environmental and social. Efforts to stimulate the hormones prolactin and oxytocin can be done with breast care or massage, oxytocin massage, nipple cleansing, early and regular breastfeeding and marmet techniques or milking and massage techniques. The "BOM" method (Breastcare, Oxytocin Massage, and Marmet Technique) is a stimulation to help the production and release of breast milk through breast care, oxytocin massage (massage or stimulation of the spine) and marmet technique (a combination of expressing breast milk and massaging the breasts) ). Mothers breastfeeding babies aged 0-6 months at Public Health Clinic Prambon Nganjuk Regency in a preliminary study of 5 (five) mothers breastfeeding babies aged 0-6 months, do not know how to make a lot of milk production using "BOM" through structured interviews. The research objective was to assess the effectiveness of the BOM (Breastcare, Oxytocin, and Marmet Teachnique) method in increasing breast milk production. This study uses a quasi-experimental method. It was carried out at the Prambon Health Center with a total sample of 60 people and used the Mann Whitney U Test analysis. The results obtained from 60 samples were a p value of 0.000 <0.05, so it can be concluded that there were significant differences between the two groups, where the BOM method (Breastcare, Oxytocin, and Marmet Teachnique) was very effective on breast milk production.